TRANSPLANTATION: Complementing donor-specific antibody testing - Tinckam, Kathryn J. (2013)
New data suggests that among kidney transplant recipients, those whose serum contains donor-specific antibodies that bind C1q fare the worst. Although these findings are intriguing, several unanswered questions remain. Changing practice to include a C1q binding assay as standard of care in kidney transplantation would be premature.